IDENTIFIKASI PERILAKU KEBERSIHAN DIRI (PERSONAL HYGIENE) REMAJA YANG TINGGAL DI ASRAMA - Zihni Sharfina Darmizah; Ari Pristiana Dewi; Erwin Erwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Adolescence is a period of transition from childhood to adulthood characterized by physical, psychological, cognitive, and psychosocial growth. Some of adolescence in Indonesia want to continuing education in a boarding school. Adolescents who live in dormitory are susceptible to disease. Effort that can be use is improve of personal hygiene behavior in the dormitory. The purpose of this study to describe the adolescence’s personal hygiene who live in dormitory. This research did at the Middle School of Babussalam Bording School used a descriptive research design. The sample of this study was 75 people taken by the proportionate stratified random sampling technique using a lottery. The results of this study are dental and oral hygiene behavior with the highest score to female gender respondents are 28 people (71,8%). Based on the results of these studies it is expected that adolescents and Islamic Boarding Schools can increase efforts like socializing about how to do right of personal hygiene so that the adolescence’s health status will increase. Keywords: Adolescence, Behavior, Dormitory, Personal Hygiene